2010
DOI: 10.1007/s12613-010-0318-4
|View full text |Cite
|
Sign up to set email alerts
|

Tool life modeling for evaluating the effects of cutting speed and reinforcements on the machining of particle reinforced metal matrix composites

Abstract: The wear of cutting tools in the machining of 2024Al alloy composites reinforced with Al 2 O 3 particles using varying sizes and volume fractions of particles up to 23.3vol% was investigated by a turning process using coated carbide tools K10 and TP30 at different cutting speeds. Machining tests were performed with a plan of experiments based on the Taguchi method. The tool life model was developed in terms of cutting speed, size, and volume fraction of particles by multiple linear regressions. The analysis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…This may be attributed to the burnishing or honing effect produced by the rubbing of small SiC particles trapped between the flank face of the tool and the workpiece surface 23 . Similar results were obtained by many other researchers and reported that during the machining of SiCp reinforced composites with both carbide and PCD inserts 5,7,12 . At lower cutting speeds the surface roughness is high due to the inability of the cutting tool to cut these particles, therefore, a high cutting speed is required to machine this composite 13 .…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…This may be attributed to the burnishing or honing effect produced by the rubbing of small SiC particles trapped between the flank face of the tool and the workpiece surface 23 . Similar results were obtained by many other researchers and reported that during the machining of SiCp reinforced composites with both carbide and PCD inserts 5,7,12 . At lower cutting speeds the surface roughness is high due to the inability of the cutting tool to cut these particles, therefore, a high cutting speed is required to machine this composite 13 .…”
Section: Resultssupporting
confidence: 91%
“…This is due to the presence of hard ceramic particles in composites, which acts as small cutting edges resulting in poor surface finish. Sometimes the hard-reinforced ceramic particles in the matrix will not be sheared off by cutting, but they are removed from the matrix, thereby creating voids on the surface 5,6 . The machining conditions greatly influence the machining characteristics of metal matrix composites.…”
Section: Introductionmentioning
confidence: 99%
“…The findings obtained are similar to previous researchers. From Kök's (2010) analysis and Muthukrishnan et al's (2008), both found that tool life was dependent on cutting speed in machining MMC and was concluded as the most significant factor. Another researcher, Seeman et al (2010) found that the deterioration of cutting tool life was detected at higher cutting speeds.…”
Section: Effect Of Cutting Parameters On the Tool Wearmentioning
confidence: 99%
“…They occur due to the matrix material smeared on the tool face where the larger sizes of hard particle reinforcements scratch and form grooves on the tool face. Kök (2010) carried out research to evaluate the effect of reinforcements on the machining of MMC with single layer (K10) and triple layer (TP30) coated carbide tool inserts under drying cutting speed ranges from 100 m/min to 210 m/min. He reinforced the MMC with larger size particles from 16 to 66 µm.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the wire electrical discharge machining (WEDM) is proven as an effective and economical method for machining MMCs into complex contours [19,20]. It is a thermo-electrical process where the metal removal takes place in a series of electric sparks discharges at the interface of continuously supplied wire (electrode) and the workpiece in the presence of dielectric medium in its working principle.…”
Section: Introductionmentioning
confidence: 99%